Organic hole-transporting materials for 9.32%-efficiency and stable CsPbBr3 perovskite solar cells. (15th October 2018) - Zhao, Yuanyuan; Liu, Tianshu; Ren, Fumeng; Duan, Jialong; Wang, Yudi; Yang, Xiya; Li, Qinghua; Tang, Qunwei
Abstract : Cost-effective and stable CsPbBr3 -based inorganic perovskite solar cells (PSCs) are made by using small-molecule BT-BTH and conjugated PEDOT, PPy and PANi as HTMs, yielding PCEs of 9.32%, 8.36%, 8.32% and 7.69%, respectively. The inorganic PSCs present good moisture tolerance in 70% humidity over 80 days. Abstract : Cost-effective and stable CsPbBr3 -based inorganic perovskite solar cells (PSCs) are regarded as promising candidates for next-generation photovoltaics. However, the large interfacial energy differences at the CsPbBr3 /hole-transporting layer lead to serious charge recombination and poor charge extraction kinetics. Herein, we prepare a series of hole-transporting materials (HTMs) to improve hole extraction and to reduce electron–hole recombination at the CsPbBr3 /HTM interface. In comparison with the power conversion efficiency (PCE) of 6.10% for an HTM-free device, the CsPbBr3 PSCs with polymeric HTMs such as polythiophene, polypyrrole and polyaniline yield efficiencies of 8.36%, 8.32% and 7.69%, respectively. Similarly, the inorganic PSC with organic small molecule BT-BTH achieves a PCE as high as 9.32% due to the improved hole conductivity. Moreover, the unencapsulated PSC with BT-BTH maintains 94% of its initial efficiency in 70% relative humidity over 80 days.